Community Service Program for Mentoring Organizational Leaders in Shaping Character-Building Students at Dayah Raudhatun Najah, Langsa City - Murni, Murni; Yeni, Manovri; Usman, Musliadi Bin (Asian Journal of Community Services, 2024)
The mentoring program conducted at Dayah Raudhatun Najah aims to instill honesty in students through structured training and activities. After the initial training, the administrators implement this program by providing direct guidance, interactive sessions, and periodic evaluations. Although the program has shown positive results, several challenges have arisen, including limited time, varying levels of understanding among administrators and students, and a lack of supporting resources. Time constraints hinder the full engagement of participants and the depth of material that can be covered. To address this, it is recommended to extend the program duration or divide it into shorter but more frequent sessions. Differences in understanding levels can be overcome with additional training for administrators and more structured program planning.